DOWNSTREAM PROCESS OF BIOPHARMACEUTICALS - D. A. Gusarov (Разработка и регистрация лекарственных средств)
The development of the biopharmaceuticals begins with the development of effective producers. But the more complex protein and its producer, the greater the amount of impurities is synthesized or accumulated during the upstream process. Among them are as follows: bacterial endotoxins, viruses, host cell proteins, related impurities, aggregates and high molecular weight admixtures etc. This article describes approaches to the downstream process purification of biopharmaceutical proteins. We discuss the main chromatography and non-chromatographical methods.